National trends in laryngectomy and the influence of hospital volume on short-term outcomes in Brazil: A 16-year cross-sectional analysis - Rafael Filipe Dal Ben Martins; Bruna Andressa Quirino; Leandro Luongo Matos; Marcelo Passos Teivelis; Nelson Wolosker; Ana Kober Nogueira Leite (Brazilian Journal of Otorhinolaryngology)
Objective: Analyze the trends and outcomes of total laryngectomy in Brazil, focusing on the influence of surgical volume on mortality. Methods: A retrospective, population-based study was conducted using data from the Brazilian Unified Health System (SUS) between 2008 and 2023. Total laryngectomies were identified through specific procedure codes, and hospitals were categorized into quartiles based on surgical volume. The number of procedures over time, mortality rates, and hospital characteristics were analyzed. Results: A total of 8884 total laryngectomies were performed, decreasing from 1142 in 2008 to 289 in 2023, a 75% reduction (APC = −9.06% per year, p < 0.001). The overall in-hospital mortality rate was 2.7% with no significant change over time Hospitals performing less than two procedures per year had significantly higher mortality rates (3.14%). However, after excluding very low-volume hospitals, mortality rates were similar among the remaining groups. Conclusion: There was a significant reduction in total laryngectomies in Brazil over the years, suggesting a shift to nonoperative treatment. Moreover, increased mortality in very low-volume hospitals underscores the need for regionalization policies to centralize complex procedures in experienced centers.